Successful treatment of gallbladder dyskinesia by laparascopic cholecystectomy: Report of a case. Issue 4 (November 2014) - Sasaki, Takamitsu; Kato, Daisuke; Shinya, Satoshi; Nakashima, Ryo; Shiwaku, Hironari; Yamashita, Kanefumi; Yamashita, Yuichi
Abstract A 75‐year‐old woman entered the hospital emergency room complaining of severe epigastric pain. She had experienced similar repeated abdominal pain for some time. Biliary tract dyskinesia was suspected based on the Roma III criteria. When drip infusion cholangiography‐CT with egg yolk load was performed, the contraction rate of the gallbladder before and after applying the load was as low as 33.5%. Upon biliary tract scintigraphy, biliary excretion into the intestinal tract was found to be normal, but after the egg yolk load, the biliary excretion rate in the gallbladder decreased to 14.5%. Laparoscopic cholecystectomy was performed under a diagnosis of flaccid‐type gallbladder dyskinesia. A few reports exist describing cases in which cholecystectomy was performed for gallbladder dyskinesia, so we are submitting this report with some bibliographic consideration.